2017
DOI: 10.1159/000456612
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Comparison of a Novel Buprenorphine Oral Lyophilisate versus Existing Buprenorphine Sublingual Tablets in Opioid-Dependent Patients: A First-in-Patient Phase II Randomised Open Label Safety Study

Abstract: Aims: To test the safety of new buprenorphine oral lyophilisate wafer (“bup-lyo”) versus standard sub-lingual buprenorphine (“bup-SL”). Design: Randomised (2:1) open-label study; opioid-dependent subjects; subsequent partial cross-over. Settings: Specialised clinical trials facility and addictions treatment facility. Participants: Opioid-dependent subjects (n = 36) commencing buprenorphine maintenance (personalised dose-titration) including patients co-using alcohol, cocaine and benzodiazepines (below threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
0
9
0
1
Order By: Relevance
“…Based on this unique feature of opioid drugs, first dose titration is emphasized in the initial clinical opioid or opiate dose adjustments to ensure safe and effective individualized drug use. 4 Due to the slow onset of oral morphine, patients need to adjust the dose several times to obtain accurate opioid demand. It usually takes 2-3 days to complete one titration, or even longer.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this unique feature of opioid drugs, first dose titration is emphasized in the initial clinical opioid or opiate dose adjustments to ensure safe and effective individualized drug use. 4 Due to the slow onset of oral morphine, patients need to adjust the dose several times to obtain accurate opioid demand. It usually takes 2-3 days to complete one titration, or even longer.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent development is a buprenorphine oral lyophilisate wafer which has been shown to be as effective as the sublingual tablet but which dissolves much more rapidly. 55…”
Section: Current Methods Of Treatmentmentioning
confidence: 99%
“…A very recent development is a buprenorphine oral lyophilisate wafer which has been shown to be as effective as the sublingual tablet but which dissolves much more rapidly. 55 It can be concluded that buprenorphine may not be the preferred treatment for many patients, especially those with complex needs. However, it is a valuable option for patients who have a relatively stable life but whose drug use has temporarily got out of control.…”
Section: Buprenorphinementioning
confidence: 99%
“…Historically, these medications have almost always been taken daily, in liquid/linctus or tablet//film form, with injectables occasionally provided to patients who repeatedly fail to benefit from oral formulations . Opioid agonist treatment is closely monitored by regulatory authorities and clinicians, and medication consumption is often physically supervised in a drug treatment or community pharmacy setting .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients have complained that the process of frequent dosing is stigmatising, restricts their freedom, and undermines their quality of life by making it difficult to work, take a holiday, and participate in other everyday activities . Unsurprisingly, therefore, poor/non‐adherence and treatment dropout are common in MAT .…”
Section: Introductionmentioning
confidence: 99%